2007
DOI: 10.1097/mnh.0b013e3280403c4e
|View full text |Cite
|
Sign up to set email alerts
|

The inflammatory response to ischemic acute kidney injury: a result of the ‘right stuff’ in the ‘wrong place’?

Abstract: The concepts discussed in this review are important for clinical medicine. Drugs and genetic manipulation may ameliorate ischemic kidney injury by regulating the inflammatory response to cell injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 135 publications
1
49
0
Order By: Relevance
“…RAGE is expressed in a wide range of renal cells and mediates a variety of inflammatory responses in renal diseases [7] , but its role in renal I/R injury was unknown [13] . Therefore, we investigated the contribution of RAGE in renal I/R.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RAGE is expressed in a wide range of renal cells and mediates a variety of inflammatory responses in renal diseases [7] , but its role in renal I/R injury was unknown [13] . Therefore, we investigated the contribution of RAGE in renal I/R.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the role of RAGE in I/R injury is tissue specific. RAGE is a multiligand receptor of the immunoglobulin (Ig) superfamily and is expressed on a wide range of cell types, including renal mesangial cells, (proximal) tubuli, podocytes and Bowman's capsule [3][4][5][6]13] . In line with these results, we showed RAGE expression on podocyte and tubuli but also on cells of the collecting duct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24,59 Release of HMGB1 has been reported after IRI. 58,[60][61][62] Data from Lu et al 63 and our findings 25 demonstrate that the ischemic kidney is the originator of surging HMGB1 in the circulation, that endothelial cells contribute to it, and that uric acid signaling can mimic this process both in vitro and in vivo. We showed that after ischemic insult, HMGB1 is released into the renal circulation within 1-3 hours (Figure 1, B and C).…”
Section: Systemic Inflammation: Three Waves Of Danger Signalingmentioning
confidence: 99%